Application of mitomycin in the treatment of cicatricial complications after radical prostatectomy - Yu. G. Alyaev; L. M. Rapoport; D. G. Tsarichenko; A. V. Artemov (Андрология и генитальная хирургия, 2014)
At a choice of a way of treatment of the localized prostate cancer not the last place is occupied by an assessment of possible complications after the executed operation. In structure of all postoperative complications cicatricial changes take only the third place, however at calculation of absolute figures are represented as a serious world problem. The article presents the global data and our own data for the prevention of complications after performing open radical prostatectomy and also experience with Mitomycin.